Luminous : living things that light up the night - Kuo, Julia (Greystone Kids, Greystone Books, 2022)
"Kids 4 to 8 will marvel at the brightly glowing creatures and other living organisms in this stunning, poetic, and science-based exploration of bioluminescence. When it's dark out, we need light to see. But what if your body could make its own light? From acclaimed author-illustrator Julia Kuo comes a remarkable picture book about bioluminescence, the light made from living things, and its many forms: fireflies and foxfire, fungi and glow-worms, deep-sea fish and vampire squids. Kuo's radiant art portrays a young child and adult discovering different bioluminescent creatures, accompanied by simple lyrical text and informative sidebars that reveal fascinating scientific facts about each of them. An introduction to an extraordinary natural phenomenon, Luminous shines a light upon how truly wondrous the world is. Luminous features: Brilliant and unique illustrations: The depiction of vibrant bioluminescent species against an unusual black backdrop creates an unforgettable visual experience for readers. The science of bioluminescence: Shares the real-life magic of bioluminescence with sidebars about the various places and species in which bioluminescence is found. Text can be read on two levels: Kuo's simple and poetic narrative is accompanied by scientific facts about bioluminescence."--